2021
DOI: 10.4103/jpn.jpn_33_20
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal nonepileptic events in a pediatric epilepsy clinic

Abstract: A BSTRACT Aims: We aimed to study the frequency, age, and gender distribution of paroxysmal nonepileptic events (PNEs) in children referred to epilepsy clinic with the diagnosis of epilepsy. We also evaluated the therapeutic implications of correct diagnosis and co-existence of true epilepsy in this population. Settings and Design: All new patients below 18 years attending the Pediatric epilepsy out-patient clinic of PD Hinduja hospital over 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Most patients without comorbid epilepsy discontinued ASMs; however, ASMs were either initiated or continued for 11 (3.8%) patients without comorbid epilepsy. Multiple studies have shown that treatment with ASMs is ineffective and can potentially lead to adverse learning and behavioural effects in patients without epilepsy [4,[26][27][28]. The results from the current study could reflect the results found in the study by Plioplys et al [29].…”
Section: Pharmaceuticalssupporting
confidence: 83%
“…Most patients without comorbid epilepsy discontinued ASMs; however, ASMs were either initiated or continued for 11 (3.8%) patients without comorbid epilepsy. Multiple studies have shown that treatment with ASMs is ineffective and can potentially lead to adverse learning and behavioural effects in patients without epilepsy [4,[26][27][28]. The results from the current study could reflect the results found in the study by Plioplys et al [29].…”
Section: Pharmaceuticalssupporting
confidence: 83%
“…Video recordings of seizures at home and provocations with a placebo test can be helpful in differentiating epileptic seizures from other disorders. 44,45 An important point to emphasise is that PNEEs often mimic non-epileptic seizures due to the similarity of clinical symptoms such as syncope, loss of consciousness, headache, vomiting, dizziness, irregular breathing or emotional and psychological problems. 1 There is no single specialised medication or treatment method specific to PNEEs that can help young patients.…”
Section: Discussionmentioning
confidence: 99%
“…A syncope event is associated with the premonitory phase and is characterized by non-specific symptoms such as dizziness, sweating, visual blurring, nausea, palpitations, pallor, weakness, and cold skin. [ 2 ] The symptoms can occur singularly or in combination for a few seconds to 1–2 minutes. [ 2 ] Syncope occurs more often in females than in males and is more common in both genders at the age of 15 years.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] The symptoms can occur singularly or in combination for a few seconds to 1–2 minutes. [ 2 ] Syncope occurs more often in females than in males and is more common in both genders at the age of 15 years. [ 3 ] Approximately 15.0% of children experience an episode of syncope before the end of the second decade of life, and 1.0% of common pediatric emergency complaints are related to syncope.…”
Section: Introductionmentioning
confidence: 99%